2016
DOI: 10.22226/2410-3535-2016-2-93-97
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics for seven-constant rhombohedral crystals and their nano/microtubes

Abstract: Stretching 7-constant rhombohedral crystals is described in the theory of elasticity. Numerical analysis, based on the obtained analytical expressions for Young's modulus and Poisson's ratio, is showed that three of the eight 7-constant rhombohedral crystals are partial auxetics, i.e. they have a negative Poisson's ratio in some directions of stretching crystals. Minimum and maximum values of Poisson's ratio and Young's modulus, values of the average Poisson's ratio and the minimum and maximum values of Poisso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…An analysis of average Poisson's ratio have shown that all hexagonal crystals have positive Poisson's ratio [9]. We note that more than four hundred crystals with negative Poisson's ratio (auxetics) are detected for crystals of other crystalline systems [5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The least number of auxetics is found among hexagonal crystals, and the largest amount is detected among cubic crystals (more than three hundred).…”
Section: Introductionmentioning
confidence: 72%
“…An analysis of average Poisson's ratio have shown that all hexagonal crystals have positive Poisson's ratio [9]. We note that more than four hundred crystals with negative Poisson's ratio (auxetics) are detected for crystals of other crystalline systems [5][6][7][8][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The least number of auxetics is found among hexagonal crystals, and the largest amount is detected among cubic crystals (more than three hundred).…”
Section: Introductionmentioning
confidence: 72%
“…In this regard, various studies of the mechanical properties of such crystals have been conducted and their features have been described in various studies. [ 10,23–64 ]…”
Section: Introductionmentioning
confidence: 99%
“…Structures considered in the present work belong to different crystal systems. For many anisotropic materials of various crystal systems (cubic, hexagonal, rhombohedral, tetragonal , orthorhombic , monoclinic, and triclinic) negative Poisson's ratio was observed. To date, more than 450 crystals with negative Poisson's ratio (auxetic crystals) were found.…”
Section: Introductionmentioning
confidence: 99%